2023
DOI: 10.3758/s13423-023-02357-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of color and saturation on the enjoyment of real-life images

Chenyang Lin,
Sabrina Mottaghi,
Ladan Shams

Abstract: This study investigated the effects of color presence and saturation on the affective judgment of real-life images, as functions of the image’s affective valence. In the first two experiments, participants observed and rated original color photos and their grayscale versions, presented in an interleaved order across two separate experimental sessions. Color photos were rated as more pleasant than grayscale photos when image valence was positive, and more unpleasant when image valence was negative. The third ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…Meanwhile, other research studies [ 25 , 111 , 220 ] revealed that individuals with mental illness and depression post less colorful images of darker and grayer colors on social media compared to healthy controls, who prefer brighter and more vivid colors such as blue and green. These patterns potentially align with existing knowledge [ 275 ] regarding the influence of individuals’ mood on color preferences, where principal hues (e.g., red, yellow) and intermediate hues (e.g., yellow-red, blue-green) evoked higher positive emotions than achromatic colors like black and white. Specifically, Yazdavar et al [ 25 ] demonstrated a strong positive correlation between self-reported depressive symptoms and individuals’ tendency to perceive surroundings as grey or lacking colors.…”
Section: Resultssupporting
confidence: 80%
“…Meanwhile, other research studies [ 25 , 111 , 220 ] revealed that individuals with mental illness and depression post less colorful images of darker and grayer colors on social media compared to healthy controls, who prefer brighter and more vivid colors such as blue and green. These patterns potentially align with existing knowledge [ 275 ] regarding the influence of individuals’ mood on color preferences, where principal hues (e.g., red, yellow) and intermediate hues (e.g., yellow-red, blue-green) evoked higher positive emotions than achromatic colors like black and white. Specifically, Yazdavar et al [ 25 ] demonstrated a strong positive correlation between self-reported depressive symptoms and individuals’ tendency to perceive surroundings as grey or lacking colors.…”
Section: Resultssupporting
confidence: 80%